The Connection Between Essential Running Techniques and Long Jump Performance Indicators in Elementary School Learners Aged 10-11 Years - Suriani. S., Lilis Lasma (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. The primary objective of this research is to analyze the link between running technique proficiency and long jump performance in 10 to 11-year-old elementary students.Materials and methods. A sample of 28 male students, aged 10 to 11 years, was selected for this study. A cross-sectional research design was utilized to investigate the relationship between basic running techniques and long jump performance in this demographic. Pearson correlation analysis was conducted to assess the association between running methodologies and long jump effectiveness. The results of this analysis determined the strength and direction of the relationship between the two variables.Results. The analysis yielded a significant correlation coefficient of r= 0.917, with a p-value of 0.000